FAKTOR RISIKO POLA ASUH TERHADAP KEJADIAN DIARE BAYI (0-12 BULAN) DI WILAYAH KERJA PUSKESMAS KEDUNGMUNDU KECAMATAN TEMBALANG KOTA SEMARANG - Wiwin Rahma Dhiana; Retno Hestiningsih; Sri Yuliawati (Jurnal Kesehatan Masyarakat (Undip), 2017)
Diarrhea in infants is a disease that occurs due to many factors, especially those related to parenting patterns provided by parents. Not all parents apply good parenting patterns. So diarrhea remains high and the target of diarrhea reduction in Kedungmundu Health Center has not been achieved. The purpose of this research is to analyze the risk factors of parenting to the incidence of diarrhea in infants in Kedungmundu Health Center. The type of this research is observational analytic with cross sectional approach. The population in this study is 0-12 months infant in the working area of Puskesmas Kedungmundu is 1987 babies. Samples taken as many as 110, using proportional random sampling method. Analyed data using Chi square test with significance level of 5%. The results showed that the number of infants with diarrhea was 25,5%, the majority was raised by the birth parents of 71,8%, exclusively breastfeeding 70,9%, the complementary foods who qualified for 60,9%, utilized 82,7% Hand washing 70.9%, managing household waste 66,1% and most carers adopt democratic parenting. The result of relationship analysis of each variable is as follows parenting (p value = 0,025), exclusive breastfeeding (p value = 0,036), MP ASI (p value = 0,111), health service utilization (p value = 0,001), hand washing = 0,036), disposing of baby feces (p value = 0,000), household waste management (p value = 0,689) and parenting (democratic p value = 0,377), (authoritative p value = 0,181), (permisif p value = 0,884) (Neglect p value = 0.949). The conclusion of care, exclusive breastfeeding, utilization of health services, hand washing and disposing of baby feces are risk factors for diarrhea occurrence in infants (0-12 months) in the work area of Kedungmundu Puskesmas, Semarang.